Reading the Words of a Musical Portrait:: Eternal-Marguerite in Berlioz's La Damnation de Faust - Zamir, Sara (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2007)
Berlioz’s concept of the female heroine made him change the original plot of Goethe’s tragedy in some crucial respects. The most prominent change was Gretchen’s redemption (Faust is the one who is redeemed in Goethe’s Faust). The omission of the contract between Faust and Mephistopheles and of the murder of the illegitimate child born to Gretchen as a result of her affair with Faust, are two important additional modifications to Goethe’s story. The composer diverges from Goethe because of the artistic liberty enjoyed by the arts in France during the first half of the nineteenth century. By studying Marguerite’s musical characterization in La Damnation de Faust, we may therefore find out how Berlioz’s compositional process was influenced by literary aspects and by the historical underpinnings of the principle of the Eternal-Feminine.